A modeling framework to evaluate blending of seawater and treated wastewater streams for synergistic desalination and potable reuse. (1st March 2020) - Wei, Xin; Binger, Zachary M.; Achilli, Andrea; Sanders, Kelly T.; Childress, Amy E.
Abstract: A modeling framework was developed to evaluate synergistic blending of the waste streams from seawater reverse osmosis (RO) desalination and wastewater treatment facilities that are co-located or in close proximity. Four scenarios were considered, two of which involved blending treated wastewater with the brine resulting from the seawater RO desalination process, effectively diluting RO brine prior to discharge. One of these scenarios considers the capture of salinity-gradient energy. The other two scenarios involved blending treated wastewater with the intake seawater to dilute the influent to the RO process. One of these scenarios incorporates a low-energy osmotic dilution process to provide high-quality pre-treatment for the wastewater. The model framework evaluates required seawater and treated wastewater flowrates, discharge flowrates and components, boron removal, and system energy requirements. Using data from an existing desalination facility in close proximity to a wastewater treatment facility, results showed that the influent blending scenarios (Scenarios 3 and 4) had several advantages over the brine blending scenarios (Scenarios 1 and 2), including: (1) reduced seawater intake and brine discharge flowrates, (2) no need for second-pass RO for boron control, and (3) reduced energy consumption. It should be noted that the framework was developed for use with co-located seawater desalination and coastal wastewater reclamation facilities but could be extended for use with desalination and wastewater reclamation facilities in in-land locations where disposal of RO concentrate is a serious concern. Graphical abstract: Image 1 Highlights: Model framework developed to evaluate synergistic use of impaired waters. Influent blending scenarios reduce energy consumption by up to 1.7 kW h/m 3 . In influent blending cases, seawater intake and discharge flowrates decrease to approximately half. Salinity gradient energy that can be recovered is approximately 0.42 kW h/m 3 . Osmotic dilution can assist biofouling control without significantly increasing energy consumption.